2008
DOI: 10.1101/gad.1640108
|View full text |Cite
|
Sign up to set email alerts
|

ALS-linked mutant SOD1 induces ER stress- and ASK1-dependent motor neuron death by targeting Derlin-1

Abstract: Mutation in Cu/Zn-superoxide dismutase (SOD1) is a cause of familial amyotrophic lateral sclerosis (ALS).[Keywords: Amyotrophic lateral sclerosis; endoplasmic reticulum-associated degradation; endoplasmic reticulum stress; Derlin-1; ASK1] Supplemental material is available at http://www.genesdev.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
381
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 454 publications
(397 citation statements)
references
References 50 publications
14
381
0
2
Order By: Relevance
“…First, our results, like those of others studies, clearly show the UBQLN2 mutants disrupt proteostasis, leading to accumulation of misfolded proteins (13,(28)(29)(30)(31). Second, accumulating evidence suggests disturbance in proteostasis, particularly induction of the UPR, as central in disease pathogenesis caused by ALS mutations in SOD1 and C9ORF72 (45)(46)(47)(48)(49). Furthermore, disruption of proteasome function in motor neurons in mice leads to ALS-like pathology (50).…”
Section: Discussionsupporting
confidence: 86%
“…First, our results, like those of others studies, clearly show the UBQLN2 mutants disrupt proteostasis, leading to accumulation of misfolded proteins (13,(28)(29)(30)(31). Second, accumulating evidence suggests disturbance in proteostasis, particularly induction of the UPR, as central in disease pathogenesis caused by ALS mutations in SOD1 and C9ORF72 (45)(46)(47)(48)(49). Furthermore, disruption of proteasome function in motor neurons in mice leads to ALS-like pathology (50).…”
Section: Discussionsupporting
confidence: 86%
“…In these diseases and others, the formation of amyloid plaques, often observed post mortem, has long been thought to play a role in neurodegeneration, but toxicity has never been confirmed (1)(2)(3). Recent research has shown that small, soluble oligomers, rather than insoluble amyloids, are likely to be the cytotoxic species causing neurodegeneration (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). These small, soluble oligomers undergo aberrant interactions with cell machinery and activate cell death pathways, but their exact stoichiometry is not known and their properties have yet to be characterized.…”
mentioning
confidence: 99%
“…Whereas the wild-type (WT) SOD1 is a ubiquitous cytoplasmic protein, a common feature of the SOD1 mutants is that they are localized to the mitochondria (8)(9)(10)(11)(12)(13) and/or endoplasmic reticulum (ER) (14)(15)(16)(17), specifically in nervous system tissues. For instance, an association between mutant SOD1 and the ER has been implicated in the induction of ER stress (14-17), and misfolded mutant SOD1 has been found in fractions enriched for mitochondria derived from ALS-affected tissues, but not from unaffected ones (8,10,12,13,18,19).…”
mentioning
confidence: 99%